Verbal Design Modelling – Complexity, AI and product innovation - Jacopo Mascitti; Davide Paciotti (Agathón)
The constant increase in tools for content generation through Artificial Intelligence (AI) is influencing and will increasingly impact the design field. This paper analyses the application of AI technology for text-to-image conversion in the specific area of product design, particularly during the development of initial concepts, identifying significant implications for innovation in industrial products. For the first time, technology can assist designers in the product conception phase, rather than in a later stage. An experimental approach, called Verbal Design Modelling (VDM), is presented and discussed. It aims to develop innovative product concepts through AI text-to-image software, to manage the complexity of AI-designer interaction in this specific context.